GAMBARAN HISTOPATOLOGI TUMOR KELENJAR LIUR DI MANADO PERIODE JULI 2010 – JULI 2013 - Merung, Marcella P. J. (Universitas Sam Ratulangi, 2014)
Abstract: Salivary glands tumor is relatively rare. In Indonesia, there?s still no complete data about the estimated incidence of salivary glands tumor. Objective:To determine the histopathology of the salivary gland tumor in Manado from July 2010 to July 2013. Methode: This was a descriptive retrospective study. Result: There were 70 patients had salivary gland tumorswith52.9% femaleand47.1% male). By age groups found that ?16 age group for 1,4%, 17 - 30 for 28.6%, 31 ? 40 for18.%), 41 ? 50 for21.4%, 51 ? 60 for14.3%, 61 ? 70 for8.6%, ?71 for 7.1%. By classification histopathology, Pleiomorphic adenoma for 57.2%, Whartin?s tumor for 11.4%, Oncocytoma, Mucoepidermoid carcinoma, and Adenocarcinoma each for 5.7%, Adenoid cystic carcinoma for4.3%,Cystadenoma for 3.0%, Myoepithelioma, Basal cell adenoma, Canalicular adenoma, Cystadenocarcinoma,and Large cell lymphoma malignant each for 1.4%. By the location, parotis gland for 47.1%, submandibula gland for 27.1%, minor salivary gland for 12.9% and the other location for 12.9%. Conclusion: Female is more than male, the highest incidence is in the group 17-30 years old, the most common benign tumors is pleomorphic adenoma while the most common type of malignant tumors is mucoepidermoid carcinoma and adenocarcinoma. The most frequent tumor?s location is parotid gland. Keywords: Salivary glands tumor, histopathology. Abstrak: Tumor kelenjar liur merupakan tumor yang jarang ditemukan. Indonesia masih belum ada data lengkap mengenai insiden tumor kelenjar liur.Tujuan: Untuk mengetahui gambaran histopatologi tumor kelenjar liur di Manado periode Juli 2010 ? Juli 2013. Metode:Penelitian ini bersifat deskriptif retrospektif. Hasil: Dari 70 penderita tumor kelenjar liurditemukan perempuan 52,9% dan laki-laki 47,1%. Kelompok usia ?16 tahun sebanyak 1,4%, 17 - 30 tahun sebanyak 28,6%,31 ? 40 tahun sebanyak 18,6%, 41 ? 50 tahun sebanyak 21,4%, 51 ? 60 tahun sebanyak 14,3%, 61 ? 70 tahun sebanyak 8,6%, ?71 tahun sebanyak 7,1%. Berdasarkan klasifikasi histopatologi jenis Pleimorphic adenoma sebanyak 57,2%, Whartin?s tumor sebanyak 11,4%, Oncocytoma,Mucoepidermoid carcinoma, dan Adenocarcinoma masing-masing sebanyak 5,7%,Adenoid cystic carcinoma sebanyak 4,3%, Cystadenoma sebanyak 3,0%, Myoepithelioma,Basal cell adenoma,Canalicular adenoma, Cystadenocarcinoma,dan Large cell lymphoma malignant masing-masing sebanyak 1,4%. Berdasarkan lokasi tumor, kelenjar parotis sebanyak 47,1%, kelenjar submandibula sebanyak 27,1%, kelenjar liur minor sebanyak 12,9% dan lokasi yang tidak jelas sebanyak 12,9%. Kesimpulan:Penderita perempuan lebih banyak dari laki-laki, insiden tertinggi pada kelompok usia17 ? 30 tahun, tumor jinak paling banyak ditemukan adalah pleomorphic adenoma sedangkan tipe ganas adalah mucoepidermoid carcinoma dan adenocarcinoma. Lokasi tumor tersering adalah kelenjar parotis. Kata Kunci: Tumor kelenjar liur, histopatologi.